Análise de custos ocultos derivados dos acidentes de trabalho: estudo de caso na construção civil - Chaves, Talita Freire (2017)
The civil construction industry is the economic activity with the highest number of occurrences of work accidents registered in the world. Such accidents result in negative consequences for the involved in the construction production system. Among these consequences, the economic losses, that is, the expenses of work accidents, it is highlighted, and they are divided into two parts: insured costs and hidden costs. The first part is apparent, and already considered in the standard accounting of the company, and the second one is difficult to identify and measure, thus being not usually computed by the company. In this sense, this study analyzes the participation of hidden costs derived from work accidents in the calculation of the total cost of work accidents, which occurred in a construction company. The methodology used in this research is classified as a case study, with combined approach to the problem, because it is qualitative and quantitative. Results showed that any work accident would result in significant costs that are not commonly correctly allocated in standard business accounting, thus misrepresenting the real total cost of work-related accidents. It can be concluded that, once companies start to correctly measure the damage from the occurrence of work accidents, it will be evident how financially damaging for a company it is the occurrence of such accidents.